Contextualizing Islamic Brotherhood Between Nahdlatul Ulama and Salafi in the Realization of Social Harmony - Syaikhul Hadi; Aminullah Elhady; Ubaidillah (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
The contextualization of ukhuwah islamiyah (Islamic brotherhood) within the Muslim community has become a crucial issue amid increasing internal fragmentation based on ideology, particularly between Nahdlatul Ulama (NU) and Salafi. In Pasuruan, differences in religious views and social frictions often create tensions, indicating that ukhuwah is not uniformly understood or practiced but shaped by each group’s ideological construction. This study employs a qualitative approach with a sociological perspective and Alfred Schutz’s social phenomenology. Data were collected through passive participant observation, in-depth semi-structured interviews, and documentation studies, then analyzed phenomenologically through the stages of horizontalization, clustering, textural and structural description, and essence formulation. Data validity was ensured through source and technique triangulation. The study aims to: (1) describe the conceptual paradigm of ukhuwah islamiyah as understood by NU and Salafi; (2) explore how ukhuwah islamiyah is practiced in the social life of both groups in Pasuruan; and (3) explain the interpretative differences of ukhuwah islamiyah in building social harmony. The findings reveal that NU embraces an inclusive understanding of ukhuwah within the framework of the trilogy of brotherhood—islamiyah, wataniyah, and bashariyah—emphasizing tolerance, intergroup cooperation, and social harmony. In contrast, Salafi interprets ukhuwah exclusively within the boundaries of shared creed and manhaj, restricting social interaction to those with the same orientation. Field practices show complex dynamics: while cooperation exists in activities such as funeral rites (takziah) and communal work (gotong royong), ideological divides continue to weaken solidarity. These findings highlight the importance of multicultural, dialogical, and spiritual approaches to realizing ukhuwah islamiyah as a universal value that transcends sectarian boundaries and strengthens social harmony.